Significance of intramedullary T2* signal voids in the magnetic resonance imaging of paraplegic deep pain-negative dogs following intervertebral disc extrusion at short-term follow-up - Clark, Robert; Ferreira, Amy; Behr, Sebastien (Frontiers in Veterinary Science, 2023)
Introduction Dogs presenting as paraplegic without nociception due to a thoracolumbar intervertebral disc extrusion provide a difficult decision to both the clinician and the owner. The prognosis when performing surgical decompression remains guarded. Aside from significant extradural compression, these dogs often have a significant secondary spinal cord injury, which has shown to be an important factor in determining both the likelihood of developing progressive myelomalacia and the return to ambulation. Materials and methods This is a retrospective, observational, single centre study including 82 dogs presenting as paraplegic with absent nociception diagnosed with an intervertebral disc extrusion. Patients underwent MRI of the thoracolumbar spine, including a gradient echo sequence which was evaluated for the presence of intramedullary signal void artefacts. Decompressive surgery was performed, and patients were evaluated for the presence of nociception at short term follow up (at least four weeks post-surgery). Results Overall, 59.8% of patients regained nociception within the study period. This number was significantly reduced to 33.3% when multiple gradient echo signal voids were present (compared to 67.3% of dogs without signal voids). There was no significant difference in the rate of developing progressive myelomalacia between groups. Conclusions This paper adds to the existing literature and suggests that the gradient echo sequence may be of use when assessing acute spinal cord injury in the context of intervertebral disc extrusion and how it relates to prognosis.